RELIGIOUS EDUCATION CURRICULUM IN SCHOOLS AROUND THE WORLD - Mukhsin, Mukhsin (INTIHA: Islamic Education Journal, 2024)
Religion has many meaningful values for human being life. All of them need it although they are from communists. The communists, in fact however, need beliefs by using another name outside religion. This study aims to find differences and similarities regarding the implementation of religious education curriculum in schools around the world. The approach of study is a qualitative-descriptive method by studying related library sources and the results of previous researches from various countries, and then concluding the research data. The study concluded that religious values are eternal and universal ones for all people. The people in one country and other countries are different in believing what they believe and behave. However, they have sameness in getting meaning of religious values urgency for their lives. So, they desire to bring these down to their generation through education or teaching process. Many countries all over the world pay attention to this urgency. They include religious education into schools’ curriculum in which it must be studied by all students.